KOMPARASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN PROBLEM SOLVING DITINJAU DARI PENGARUHNYA TERHADAP PENCAPAIAN KEMAMPUAN BERPIKIR KRITIS PADA MUPEL IPA SISWA SD KELAS V - Hendriana Monalisa; Nyoto Harjono (PIONIR: JURNAL PENDIDIKAN, 2020)
The purpose of this research was to determine the comparative results of problem based learning (PBL) and problem solving (PS) learning models in terms of critical thinking skills in science subject content of fifth grade elementary school students. This type of research is a meta-analysis. The analysis data were obtained through online journals on Google Scholar or Scholar and after a selection of several articles was finally determined a sample of 20 relevant articles for analysis. The variable of critical thinking ability is measured through 4 indicators, namely understanding, planning, completing and checking again. Ancova test was performed to determine the difference in the effect between the PBL and PS models. The results of the Effect Size test with two learning models were Sig. of 0.003 with a partial eta squared value of 0.386. These results indicate that the PBL and PS learning models are classified as having an influence on the critical thinking skills of Science. The results of the Ancova test for the PBL learning model have an average value of 75,1154 and an average value of the PS learning model of 84.6724. So it can be concluded that the PS learning model is higher than the PBL learning model in terms of science critical thinking skills.